Design of SIW Cavity Backed Volumetric Slot Antenna for Wideband Applications - Teja Srilakshmi S; T Naga Anjali K; Anirudh CH; Ajar Naseem SK; P Durga Prasad M; Ramprasad Ravula (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In modern wireless communication systems by growing demands in wideband applications. The wideband capability of the antenna enhances its functionality by supporting a broader range of frequency spectrum and increase the data transmission. Using the slot technique, the substrate integrated waveguide cavity-backed antenna’s bandwidth can be increased. Create a slot antenna supported by a substrate integrated waveguide cavity in compliance with this, and evaluate its performance metrics, including gain, bandwidth, directivity, reflection coefficient, and radiation pattern. A substrate integrated waveguide cavity backed slot antenna that is ideal for wide band applications was suggested based on the study.